Triggering and contributing socio-economic factors to aggravated robbery : the perspective of offenders at Baviaanspoort Maximum Correctional Centre - Lombard, A. (Antoinette) (University of Pretoria, 2013)
Dissertation (MSW)--University of Pretoria, 2012.